Do educational outcomes correspond with the requirements of nursing practice: educators' and managers' assessments of novice nurses' professional competence. Issue 4 (7th February 2014) - Numminen, Olivia; Laine, Tuija; Isoaho, Hannu; Hupli, Maija; Leino‐Kilpi, Helena; Meretoja, Riitta
<x xml:space="preserve">Abstract</x> Objective This study evaluated weather educational outcomes of nurse education meet the requirements of nursing practice by exploring the correspondence between nurse educators' and nurse managers' assessments of novice nurses' professional competence. The purpose was to find competence areas contributing to the acknowledged practice–theory gap. Design A cross‐sectional, comparative design using the Nurse Competence Scale was applied. Subjects The sample comprised nurse educators (n = 86) and nurse managers (n = 141). Methods Descriptive and inferential statistics were used in the data analysis. Main outcome measures Educators assessed novice nurses' competence to a significantly higher level than managers in all competence areas (p < 0.001). The biggest correspondence between educators' and mangers' assessments were in competencies related to immediate patient care, commitment to ethical values, maintaining professional skills and nurses' care of the self. The biggest differences were in competencies related to developmental and evaluation tasks, coaching activities, use of evidence‐based knowledge and in activities which required mastering a comprehensive view of care situations. However, differences between educators' and managers' assessments were strongly associated with their age and work experience. Active and improved collaboration should be focused on areas in which the differences between educators' and managers' assessments greatly differ in ensuring novice nurses′ fitness for practice.